An advanced understanding of the heterogeneous clinical features of “non-criteria” obstetric antiphospholipid syndrome: Two case reports and a literature review - Peng, Xue; Tan, Xi; Xing, Aiyun (Frontiers in Immunology, 2023)
Antiphospholipid syndrome (APS) is an acquired autoimmune disorder characterized by recurrent venous and/or arterial thrombosis and/or pregnancy complications, in the presence of elevated antiphospholipid (aPL) antibodies. APS in pregnant women is referred to as “obstetrical” APS (OAPS). The diagnosis of definite OAPS requires the presence of one or more typical clinical criteria and persistent aPL antibodies at least 12 weeks apart. However, the classification criteria for OAPS have generated wide discussion, with a growing impression that certain patients not fully meeting these criteria might be inappropriately excluded from the classification, which is known as “non-criteria” OAPS. We present here two unique cases of potentially lethal “non-criteria” OAPS, complicating severe preeclampsia, fetal growth restriction (FGR), liver rupture, preterm birth, refractory recurrent miscarriages, or even stillbirth. We further share our diagnostic search and analysis, treatment adjustment, and prognosis for this unusual antenatal event. We will also present a short review of an advanced understanding of the pathogenetic mechanisms of this disease, heterogeneous clinical features, and potential significance.